Needs Analysis for E-Module Development in the Microteaching Course to Enhance Pedagogical Competence - Hisanan, Herawan; Pattaufi; Yusuf, Nuraini (International Journal of Education, Vocational and Social Science, 2025)
This research focused on performing a comprehensive needs analysis to guide the creation of an e-module aimed at bolstering pedagogical skills within the Microteaching course. The study particularly explored the educational hurdles faced by students, their preferred learning materials, and their expectations for digital learning within the Educational Technology program at Universitas Negeri Makassar. Data collection was facilitated through multiple methodologies, including questionnaires, interviews, and observations, involving a cohort of 20 undergraduate students. The questionnaire was meticulously designed with ten key indicators focusing on various aspects such as learning content, accessibility, interactive elements, and visual attractiveness. Findings indicated that a significant majority of students perceived existing instructional materials as inadequate and unengaging, signifying a critical need for improvements. The highest needs were related to the inclusion of clear learning objectives (93%) and offline usability (92%). These findings indicate that an e-module for the Microteaching course is needed to support flexible, independent, and engaging learning. The results of this analysis serve as a foundation for the subsequent development phase using the 4D model to improve the quality of pedagogical learning.